2018
DOI: 10.1096/fj.201700419r
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine restriction modulates renal response and attenuates kidney injury in mice

Abstract: Methionine restriction (MR) extends the lifespan across several species, such as rodents, fruit flies, roundworms, and yeast. MR studies have been conducted on various rodent organs, such as liver, adipose tissue, heart, bones, and skeletal muscle, to elucidate its benefits to the healthspan; however, studies of the direct effect of MR on kidneys are lacking. To investigate the renal effects of MR, we used young and aged unilateral nephrectomized and 5/6 nephrectomized (5/6Nx) mice. Our studies indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…A). Plasma 2 H 2 O reached maximal levels earlier in SAAR than in CD rats, likely due to higher intake of water, as shown in other studies . In order to compare rates of synthesis of 2 H‐Ala, it is important that both CD and SAAR rats have similar levels of precursor (i.e., 2 H 2 O).…”
Section: Resultsmentioning
confidence: 82%
“…A). Plasma 2 H 2 O reached maximal levels earlier in SAAR than in CD rats, likely due to higher intake of water, as shown in other studies . In order to compare rates of synthesis of 2 H‐Ala, it is important that both CD and SAAR rats have similar levels of precursor (i.e., 2 H 2 O).…”
Section: Resultsmentioning
confidence: 82%
“…Folate is the term used to describe a range of forms of the water-soluble vitamin B-9 that occurs naturally in foods (Table 1) (41,45). Dietary folate has an important role in the formation of SAM, and can be a limiting factor in the associated pathway.…”
Section: Folatementioning
confidence: 99%
“…Additionally, Met restriction may delay the progression of CKD by down-regulating inflammatory and fibrotic processes. This results in lower expression of urinary biomarkers normally elevated during kidney disease(41).Correspondingly therefore, a high Met diet may induce elevated levels of oxidative stress and elevate renal damage in kidneys with tubular hypertrophy(42,43). Surprisingly therefore, , Amaral et al(44) have reported that a high Met diet is not deleterious to kidney cells in Wistar rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that a methionine restriction (MR) extends lifespans in several species, such as rodents, fruit flies, roundworms, and yeast, possibly through an increased oxidative stress capacity and hydrogen sulfate (H 2 S) production [ 66 , 67 , 68 , 69 ]. Cooke et al recently reported that an MR attenuated a kidney injury in 5/6 nephlectomy mice by down-regulating inflammation and fibrosis mechanisms [ 70 ]. Therefore, we suspect that the reno-protective effect of a VLPD on DKD in type 2 diabetes and obesity rats in our previous studies may be exerted through methionine or other amino acid restriction.…”
Section: Closing Remarks and Expected Future Prospectsmentioning
confidence: 99%